2021
DOI: 10.53733/191
|View full text |Cite
|
Sign up to set email alerts
|

Local X-ray Transform on Asymptotically Hyperbolic Manifolds via Projective Compactification

Abstract: We prove local injectivity near a boundary point for the geodesic X-ray transform for an asymptotically hyperbolic metric even mod $O(\rho^5)$ in dimensions three and higher.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Finally the vanishing of K ∇ to infinite order on G b × [0, η 0 ) follows as in the proof of [UV16, Proposition 3.3] (also see [Ept20,p.45]), where it is shown that e − σR X 1+xR X χ P decays exponentially (or vanishes identically) as R → ∞, and upon taking into account that all other factors of the kernel grow at most polynomially fast as R → ∞, uniformly in η. Lemma 6.4. Let the hypotheses and notations of Lemma 6.3 be in effect.…”
Section: Analysis Of Kernelsmentioning
confidence: 98%
“…Finally the vanishing of K ∇ to infinite order on G b × [0, η 0 ) follows as in the proof of [UV16, Proposition 3.3] (also see [Ept20,p.45]), where it is shown that e − σR X 1+xR X χ P decays exponentially (or vanishes identically) as R → ∞, and upon taking into account that all other factors of the kernel grow at most polynomially fast as R → ∞, uniformly in η. Lemma 6.4. Let the hypotheses and notations of Lemma 6.3 be in effect.…”
Section: Analysis Of Kernelsmentioning
confidence: 98%
“…The geodesic ray transform is closely related to the boundary rigidity problem [60,68] and the spectral rigidity of closed Riemannian manifolds [22,23,56]. Other recent considerations include generalizations of many existing results to some classes of open Riemannian manifolds [18,21,24,44] and to the matrix weighted ray transforms [38,59] as well as their statistical analysis [45,46].…”
Section: Introductionmentioning
confidence: 99%